Diabetes Related Knowledge, Attitude and Practice among Diabetic Patients Attending at Chittagong Medical College Hospital (IAHS Medical Journal, 2024)
Background: Increased awareness among large population groups is a major determinant for the prevention of diabetes and its complications. Knowledge and attitude are the principal markers of awareness that need to be studied in various population groups in specific racial and cultural contexts. Therefore, good Knowledge, Attitude and Practices (KAP) regarding diabetes are necessary in promoting care. This study aimed to explore Knowledge, Attitude and Practices (KAP)-regarding Diabetes Mellitus (DM) among diabetic patients attending in Chittagong Medical College Hospital.Materials and methods: This cross-sectional study was conducted from January 2022 to December 2022 among 289 diabetic patients from the outpatient department of Chittagong Medical College Hospital, Chattogram. KAP were assessed by a pre-structured, interviewer-administered questionnaire and categorized using predefined scores of poor (